Production Rate Analysis of Citronella Essential Oil Using Distillation Method - Novi Diah Wulandari; Novi Caroko; Lilis Kurniasari; Iswanto Suwarno (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Semoyo is one of the districts located in Gunungkidul Regency. The community engages in the cultivation of traditional medicinal plants. One of the area's widely cultivated traditional medicinal plants is citronella. The community produces a significant amount of citronella, but it has yet to be processed into high-value economic products. Currently, citronella has emerged as a promising commodity because it can be used as a raw material to produce essential oil. The production of citronella essential oil is carried out through steam-hydro distillation. This research aimed to test the distillation characteristics to determine the potential production of citronella essential oil. The research aimed to determine the rate and capacity of essential oil production using citronella as the raw material. Based on the test results, the optimal duration for the distillation process of 2,000 grams of citronella was 60 minutes, with a maximum duration of 90 minutes. The yield of citronella essential oil obtained from this test was 0.414%. The resulting citronella essential oil has a density of 0.920 grams/mL, a clear appearance, a distinctive lemongrass aroma, and a light yellow color. These criteria meet the SNI 3953:2019 for citronella essential oil